Critic and reviewer – synonyms or special terms? Dictionary overview (Death of the Critic: Participatory Culture and the Transformations of Criticism in the 20th and 21st Centuries, 2022)
This article reviews dictionary definitions of the terms "criticism" and "review" (and their derivatives) over the centuries. Its purpose is to determine whether these terms can be used interchangeably, or whether they are different, defining a different system of evaluating a cultural text. In the circle of considerations carried out in the article there is also a question concerning the target audience of critics and reviewers.